PERBANDINGAN SENSITIVITAS DAN SPESIFISITAS MODEL PREDIKSI KEBANGKRUTAN PADA INDUSTRI PROPERTY DAN REAL ESTATE: PENDEKATAN ALTMAN, GROVER, SPRINGATE, DAN ZMIJEWSKI - Aquino, Afvan; Waldelmi, Idel; Elfrida, Lusiana (Jurnal Ekonomi Bisnis Kompetif, 2025)
This study examines bankruptcy prediction in property and real estate companies listed on the Indonesia Stock Exchange during 2019–2023 using four models: Altman Z-Score, Grover, Springate, and Zmijewski. The sample consists of 10 firms selected from the IDXPROPERT index. Each model applies different financial ratios: Altman (four ratios), Grover (three ratios), Springate (four ratios), and Zmijewski (three ratios). The findings indicate that, on average, three out of the four methods classify the companies as financially healthy, even during the Covid-19 pandemic. This resilience is supported by strong working capital, substantial recurring income, well-managed debt reflected in favorable Debt-to-Equity and current ratios, and positive operating cash flows. Differences in results, particularly from the Springate model, are attributed to its use of the asset turnover ratio, which is less appropriate for property and real estate firms and more suitable for manufacturing companies, leading to variation in bankruptcy risk classification.